Notes on "A checklist of the Gyrinidae (Coleoptera: Adephaga) of Brazil" by Colpani et al. (2014) - Fery, H.; Benetti, C.j.; Colpani, D.; Hamada, N. (Zootaxa, 2015)
In a recently published paper on the Gyrindae of Brazil (Colpani et al. 2014) a checklist of all known species from this country was given. This addition to the knowledge of Gyrinidae, based on literature published prior to 2012, comprises 206 species and subspecies and gives a complete account of the nomenclature for each taxon including synonyms and historical combinations. Additionally, the geographical distribution–both inside and outside of Brazil–of each species is provided. Although the authors have studied the literature (about 120 publications, most of them in French or German) very carefully, it was quite inevitable that some mistakes were made.